Access to Public Health Services: A Disaggregated Analysis of Uttar Pradesh. (August 2014) - Tripathi, Tulika; Mishra, Nripendra Kishore
Access to public health care has often been equated with health outcomes. Outcomes-based analysis often misunderstands the process of access to health. This article conceives access to health as a bundled concept and decomposes access into availability, affordability and acceptability. Access to health is determined by public provisioning as well as by socio-economic characteristics of households. It attempts to examine these dimensions across different regions of the Indian state of Uttar Pradesh (UP). It shows that there are variations across regions and socio-economic characteristics of households. A particular group from one region may not have the same degree of access as its counterpart in another region and at the same time there are variations across groups in the same region. The scale of development of regions also plays an important role in promoting or hindering access to health. JEL Classification: I12, I14, I18, Z13, N35, H51